Cervical vestibular evoked myogenic potentials in 3-month-old infants: Comparative characteristics and feasibility for infant vestibular screening - Shen, Jiali; Wang, Lu; Ma, Xiaobao; Chen, Zichen; Chen, Jianyong; Wang, Xueyan; He, Kuan; Wang, Wei; Sun, Jin; Zhang, Qin; Shen, Min; Chen, Xiangping; et al. (Frontiers in Neurology, 2022)
Objective: We compared the characteristics of air-conducted sound cervical vestibular evoked myogenic potential (ACS-cVEMP) and bone-conducted vibration cVEMP (BCV-cVEMP) among 3-month-old infants with normal hearing and sensorineural hearing loss (SNHL), and healthy adults to explore the feasibility and optimal strategies for infant vestibular screening. Methods: 29 infants (58 ears) were divided into two groups according to hearing (group I: normal hearing ears; group II: SNHL ears), 20 healthy adults were defined as group III. The results of response rate, P13 and N23 latency, P13-N23 interval, amplitudes, and corrected interaural asymmetry ratio (IAR) were recorded and compared among three groups. Results: The response rates of ACS-cVEMP in three groups were 88.89%, 62.00%, 100%, respectively. The P13 and N23 latencies, and P13-N23 interval did not differ significantly between group I and II (p=0.866, p=0.190, p=0.252). A significant difference was found between group I and III (p=0.016, p＜0.001, p＜0.001). No significant difference was observed in raw or corrected amplitude between group I and II (p=0.741, p=0.525), while raw and corrected amplitudes in group III were significantly larger than group I (p＜0.001, p＜0.001). For BCV-cVEMP, the response rates were 100%, 86.36%, 100%, respectively, No significant difference existed in the P13 and N23 latency, or P13-N23 interval between group I and II (p=0.665, p=0.925, p=0.806), however, P13 and N23 latencies were significantly longer in group III than group I (p＜0.001, p=0.018), but not in P13-N23 interval (p=0.110). There was no significant difference in raw or corrected amplitude between group I and II (p=0.771, p=0.155) or in raw amplitude between group I and III (p=0.093), however, a significant difference existed in corrected amplitude between group I and III (p＜0.001). Conclusions: Compared with adults, 3-month-old infants with normal hearing presented with equivalent response rates, shorter P13 and N23 latencies, smaller corrected amplitudes, and a wider IAR range for both ACS and BCV-cVEMP. SNHL infants had equivalent response rates of BCV-cVEMP, lower response rates of ACS-cVEMP than normal hearing infants. When responses were present, characteristics of ACS and BCV-cVEMP were similar with normal hearing infants. ACS combined with BCV-cVEMP are recommended to improve the accuracy of vestibular screening.